Intakes of major food groups in China and UK: results from 100,000 adults in the China Kadoorie Biobank and UK Biobank - Papier, K; Kakkoura, M; Guo, Y; Tong, T; Perez Cornago, A; Chang, WC; Chen, Z; Du, H; Key, T (Springer Nature, 2022)
Purpose Different populations may exhibit differences in dietary intakes, which may result in heterogeneities in diet–disease associations. We compared intakes of major food groups overall, by sex, and by socio-economic status (SES) (defined as both education and income), between participants in the China Kadoorie Biobank (CKB) and the UK Biobank (UKB). Methods Data were from ~ 25,000 CKB participants who completed a validated interviewer-administered computer-based questionnaire (2013–2014) and ~ 74,000 UKB participants who completed ≥ 3 web-based 24-h dietary assessments (2009–2012). Intakes of 12 major food groups and five beverages were harmonized and compared between the cohorts overall, by sex and by SES. Multivariable-adjusted linear regression examined the associations between dietary intakes and body mass index (BMI) in each cohort. Results CKB participants reported consuming more rice, eggs, vegetables, soya products, and less wheat, other staple foods (other than rice and wheat), fish, poultry, all dairy products, fruit, and beverages compared to UKB participants. Red meat intake was similar in both cohorts. Having a higher SES was generally associated with a higher consumption of foods and beverages in CKB, whereas in UKB dietary intakes differed more by education and income, with a positive association observed for meat and income in both UKB and CKB but an inverse association observed for education in UKB. Associations of dietary intakes with BMI varied between the two cohorts.